Comprehensive insights into UTIs: from pathophysiology to precision diagnosis and management - Sujith, Swathi; Solomon, Adline Princy; Rayappan, John Bosco Balaguru (Frontiers in Cellular and Infection Microbiology, 2024)
Urinary tract infections (UTIs) are the second most common infectious disease, predominantly impacting women with 150 million individuals affected globally. It increases the socio-economic burden of society and is mainly caused by Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Enterobacter spp., and Staphylococcus spp. The severity of the infection correlates with the host factors varying from acute to chronic infections. Even with a high incidence rate, the diagnosis is mainly based on the symptoms, dipstick analysis, and culture analysis, which are time-consuming, labour-intensive, and lacking sensitivity and specificity. During this period, medical professionals prescribe empirical antibiotics, which may increase the antimicrobial resistance rate. Timely and precise UTI diagnosis is essential for addressing antibiotic resistance and improving overall quality of life. In response to these challenges, new techniques are emerging. The review provides a comprehensive overview of the global burden of UTIs, associated risk factors, implicated organisms, traditional and innovative diagnostic methods, and approaches to UTI treatment and prevention.